The Staphylococcus aureus α-Acetolactate Synthase ALS Confers Resistance to Nitrosative Stress - Carvalho, Sandra M.; de Jong, Anne; Kloosterman, Tomas G.; Kuipers, Oscar P.; Saraiva, Lígia M. (Frontiers in Microbiology, 2017)
Staphylococcus aureus is a worldwide pathogen that colonizes the human nasal cavity and is a major cause of respiratory and cutaneous infections. In the nasal cavity, S. aureus thrives with high concentrations of nitric oxide (NO) produced by the innate immune effectors and has available for growth slow-metabolizing free hexoses, such as galactose. Here, we have used deep sequencing transcriptomic analysis (RNA-Seq) and 1H-NMR to uncover how S. aureus grown on galactose, a major carbon source present in the nasopharynx, survives the deleterious action of nitric oxide. We observed that, like on glucose, S. aureus withstands high concentrations of NO when using galactose. Data indicate that this resistance is, most likely, achieved through a distinct metabolism that relies on the increased production of amino acids, such as glutamate, threonine and branched-chain amino acids. Moreover, we found that under NO stress the S. aureus α-acetolactate synthase (ALS) enzyme, which converts pyruvate into α-acetolactate, plays an important role. ALS is proposed to prevent intracellular acidification, to promote the production of branched-chain amino acids and the activation of the TCA cycle. Additionally, ALS is shown to contribute to the successful infection of murine macrophages. Furthermore, ALS contributes to the resistance of S. aureus to beta-lactam antibiotics such as methicillin and oxacillin.